Evaluation of the SB 1041 Reforms to California's CalWORKs Program Background and Study Design - Karoly, Lynn A. (RAND Corporation, 2015)
This report provides background on the Senate Bill (SB) 1041 reforms to the California Work Opportunity and Responsibility to Kids (CalWORKs) program, as well as an overview of a multiyear, multicomponent evaluation of the SB 1041 policy changes. The authors motivate and summarize the CalWORKs reforms, delineate the questions underlying the evaluation, and explain the evaluation approach, timetable, products, and expected utility.